Usability Evaluation and Improvement of iGracias Mobile Application Design Using Usability Testing Method With user-centred Design Approach - Sandan, Ferrari Arya Denaya; Raharja, Pradana Ananda; Gustalika, Muhammad Azrino (Politeknik Piksi Ganesha Indonesia, 2023)
An academic information system is a system designed to process educational data. IGracias Mobile is a theoretical information system application that can be used flexibly by Telkom Purwokerto Institute of Technology students. iGracias aims to provide information about lectures to students. iGracias can be downloaded via google playstore. Based on a questionnaire involving students of the Telkom Purwokerto Institute of Technology, they found several problems with the iGracias application so that it could be maximized to provide lecture information to students. Based on the evaluation of the current design using the System Usability Scale (SUS) questionnaire, the contemporary design has a score of 58, which is classified as grade D with a bad adjective rating, so the design needs to be improved. The method used to develop and develop the user interface design on the iGracias Mobile application is the Usability Testing method with a user-centred Design approach. The results obtained from this study are a new design for the iGracias Mobile application, which was made based on the respondents' suggestions and the steps involved in the UCD method. This research found that the new design's usability value has increased from 58 to 80.8, which is included in grade A with an adjective rating of excellent. Then the new design can overcome the problems in the iGracias Mobile application.